Mode-specific, semi-volatile chemical composition of particulate matter emissions from a commercial gas turbine aircraft engine. (1st December 2019) - Yu, Zhenhong; Timko, Michael T.; Herndon, Scott C.; Miake-Lye, Richard, C.; Beyersdorf, Andreas J.; Ziemba, Luke D.; Winstead, Edward L.; Anderson, Bruce E.
Abstract: We measured and characterized semi-volatile chemical composition of particulate matter (PM) in aircraft engine exhaust plumes in a dedicated aircraft PM emission study (NASA's AAFEX 1 field measurement campaign). Mode-specific organic and sulfate components were observed with a compact time-of-flight aerosol mass spectrometer (C-ToF-AMS). Nitrate components in both the nucleation and soot mode particles were negligible. The organic composition for the nucleation mode particles decreases with increasing engine power. For the soot mode, organic fraction initially decreases with increasing engine power but then slightly increases again above 45% engine thrust, probably due to the increasing contribution from lubrication oil emissions. These results show that an appreciable amount of semi-volatile PM can be generated in the exhaust plumes from a commercial aircraft engine. Thus, volatile PM must be studied as carefully as non-volatile soot emissions to fully address local air quality and human health impacts of aviation. Highlights: Semi-volatile PM emissions of a commercial aircraft engine were characterized. Organic and sulfate contributions to nucleation and soot modes were quantified. Lubrication oil emissions dominate at high thrust. Volatile PM must be investigated to address environmental impacts of aviation.